Applying spent coffee ground as an organic soil ameliorant in the Limpopo Province, South Africa - Motlanthi, Mahlatse (My University, 2022)
The constant growth experienced by the coffee industry has led to the high-volume production of coffee waste worldwide. One of the main coffee wastes is spent coffee ground (SCG), a residue obtained after the ground coffee beans are treated under pressure. The present study was aimed to investigate the utilization of SCG to amend soil physicochemical properties. This study was conducted at Greenhouse Biotechnologies Research Centre of Excellence, University of Limpopo, South Africa, where the effect of various rates of SCG concentration in volume percentage (vol%) was tested for a period of nine months. The spent coffee ground residue was collected from four restaurants at Haenertsburg, and the application rates were 0, 5, 10, 20, 30, 50 vol%. To evaluate the change in soil physicochemical properties overtime, the incubation period was divided into four test periods namely T1 was after a month, T3 after 3 months, T6 after 6 months, and T9 after 9 months. Physicochemical properties including nitrogen (N), phosphorus (P), potassium (K), magnesium (Mg), calcium (Ca), total organic carbon (TOC), cadmium (Cd), copper (Cu), nickel (Ni), zinc (Zn), and lead (Pb), pH, electrical conductivity (EC), C:N ratio, large macroaggregates (LM), small macroaggregates (sM), microaggregates (m), unaggregated silt and clay (s+c), mean weight diameter (MWD) and soil moisture content (SMC) were quantified at the end of each test period. Results revealed that the interaction between incubation periods and various SCG application rates significantly (p<0.05) increased pHw, EC, MWD, LM, base cations and significantly decreased TOC, heavy metals, SMC, m, and sM. Spent coffee ground increased pHw and EC of the soil at all application rates and reached a maximum of 7.8 units at T6 in treatment SCG-5 and 202.30 S/cm at T9 in treatment SCG-50 above the control respectively. Total organic carbon increased by 548% above control in the highest treatment (SCG-50) at T1, but, however, started declining from T3 in all treatments across the incubation period. SCG’s highest application rates (SCG-20 to SCG-50) reduced the soil Cd toxicity (threshold of >2 mg/kg), but however, also reduced the availability of micronutrients (Cu and Zn) during the incubation period. At T9, Mg, Ca, K, and P increased from mean values of 55.9 to 77.9, 40.9 to 62.2, 77.4 to 112, and 22.0 to 30.0 mg/Kg above control in treatments with high application rates. LM increased whilst sM, and m decreased across the incubation period in all treatments. MWD increased by 46% at T1 and reached its maximum of 56% at T6 in treatment SCG-50 above control. Additionally, there was a positive relationship between LM and MWD. Soil moisture content however increased to 60.26% at T1 in treatment SCG-50 and decreased from T3 across the incubation period. Spent coffee ground has the potential to be used as a liming material, a chelating agent, and for water management in semi-arid areas. It retains and cycles nutrients and improves soil structure through aggregation. However, research should be done in field conditions to access the effectiveness of this residue.
Thesis (M.Sc. Agriculture. (Soil Science)) -- University of Limpopo, 2022
Keywords: Spent coffee ground; Bio-waste; Incubation period; Soil amelioration; Soil fertility; Sandy loam soil; Heavy metal toxicity; Soil fraction and stability; Soil moisture content; Soil fertility; Coffee grounds; Soils -- Heavy metal content; Soil pollution; Coffee grounds